Elevated ambient temperature reduces fat storage through the FoxO-mediated insulin signaling pathway - Tucker Hopkins; Cole Ragsdale; Jin Seo (PLoS ONE, 2025)
Temperature profoundly impacts all living organisms, influencing development, growth, longevity, and metabolism. Specifically, when adult flies are exposed to high temperatures, there is a notable reduction in their body fat content. We investigate the roles of the insulin signaling pathway in temperature-mediated fat storage. This pathway is not only highly conserved from insects to mammals but also crucial in regulating lipid metabolism, cell proliferation, and tissue growth. The Forkhead box O (FoxO) protein functions as a key downstream signaling molecule in this pathway, mediating the inhibitory effects of insulin signaling. At elevated temperatures, direct targets of FoxO, such as insulin receptor (InR), Thor (Drosophila eukaryotic initiation factor 4E binding protein), and FoxO itself, are significantly upregulated, which indicates an inhibition of insulin signaling. Interestingly, this inhibition seems to occur independently of Drosophila insulin-like peptide (Ilp) stimuli, as not all Ilp transcripts were reduced at elevated temperatures. Furthermore, when S2R + Drosophila cells are incubated at high temperatures, there is a marked decrease in Akt phosphorylation, directly supporting the notion that elevated temperatures can inhibit insulin signaling in a cell-autonomous manner, independent of Ilp levels. Subsequent experiments demonstrated that either constitutively active InR or knockdown of FoxO prevents the reduction of body fat at high temperatures. Together, these findings highlight the critical role of the insulin signaling-FoxO branch in regulating lipid homeostasis under heat stress conditions.